A new risk factor? Diagonal earlobe crease (Frank's sign) associated with intracranial aneurysms: a case–control study - Victor Ramzes Chavez-Herrera; Bayron A. Sandoval-Bonilla; Joel Abraham Velazquez-Castillo; Pedro Adrian Gonzalez-Zavala; Flavio Hernandez-Gonzalez; Felix Adrian Vergara-Martinez; Anabel Saldaña-Gonzalez; Miguel Abdo-Toro; Blas Ezequiel Lopez-Felix; Ivan Tellez-Medina; Martin Paredes-Cruz; Rabindranath Garcia-Lopez (World Neurosurgery: X)
Objective: To evaluate the association of diagonal earlobe crease (DELC, Frank's sign), laterality, and type of DELC with the presence of intracranial arterial aneurysms (IAA). Methods: The authors conducted a hospital-based case–control study involving 130 patients diagnosed with IAA and 130 age-grouped and sex-matched controls who had no arterial intracranial aneurysms. This study aimed to evaluate a potential association between IAA and DELC, the laterality of DELC, and the type of DELC. Multivariable logistic regression models were applied to identify correlations between cases and controls. Results: DELC was identified in 96 patients of the IAA group (73.8 %) and 45 in the control group (34.6 %). There was a significant association between IAA and DELC (OR 7.92, 95 % CI 3.96–15.83, p < 0.001), unilateral and bilateral DELC (OR 7.36, 95 % CI 2.96–18.31, p < 0.001, and OR 8.17, 95 % CI 3.90–17.14, p < 0.001, respectively), and type 2, type 3, and type 4 DELC (OR 5.66, 95 % CI 2.17–14.77, p < 0.001, OR 5.73, 95 % CI 1.95–16.83, p 0.001, and OR 39.45, 95 % CI 12.40–125.50, p < 0.001, respectively). Type 1 DELC was not associated with IAA (p 0.079). Conclusions: This study demonstrates a significant association between DELC and the presence of IAA. Laterality was not a limiting factor. Complete and deep features in DELC are associated with IAA, whereas superficial incomplete DELC is not. Hypertension also showed an association with IAA. DELC should be considered a risk factor for IAA. DELC could serve as a crucial candidate risk factor for determining prognosis and screening protocols for patients with IAA; this may enable timely interventions to improve outcomes.